Sistem Pakar Deteksi Penyakit Bawang Merah dengan Metode Case Based Reasoning - Yohani Setiya Rafika Nur; Auliya Burhanuddin; Dasril Aldo; Widya Lelisa Army (STMIK Budi Darma, 2022)
Shallots are tubers commonly consumed by Indonesians. Shallots are one of the three members of the Allium genus that are much-loved and have high economic value. In the process of cultivating shallots susceptible to pests and diseases. Onion caterpillars, leaf flies, earthworms, purpura, fusarium wilt, onion mosaic and leaf spot are some of the pests and diseases that often attack shallot plants. Farmers will immediately give pesticides or methods that are sometimes not suitable for pests and diseases that attack. As a result, maintenance is not optimal and new pests or diseases often arise. This study aims to help farmers find early symptoms of shallot pests and diseases, so that pest and disease control is more optimal and on target. Processed as many as 10 attack data using Case Based Reasoning method. This method will process data in the form of symptoms seen in shallots, so that they can detect types of pests and diseases of shallots and their handling steps with 100% accuracy. Therefore, this method is relevant for the identification of shallot disease